IDEOLOGI DI BALIK SIMBOL-SIMBOL SURGA DAN KENIKMATANNYA DALAM AYAT-AYAT QURAN - Taufiq, Wildan (Universitas Muhammadiyah Surakarta, 2008)
Â As a system of symbol, the language of Holy Quran has interesting phenomena because there are many concrete illustrations of Heaven and its delicacies explained inside, for example, Heaven symbolized as garden containing fruits (kurma and grape), drinks (beer, milk, honey), accessories (gold bracelet, pearl), and (silk) cloths; and beautiful wives like angels. Such an illustration is contradictory to the most Moslemsâ belief for they assume that based on the Quran and Hadith, Heaven is abstract. This article is aimed to reveal âthe ideologyâ beyond the Heaven and its delicacies viewed from semiotics. The study shows that behind the symbols of Heaven and its delicacies, there is a spiritualistic-materialism ideology. The Quran includes such symbols because the Arabian community thinks that Heaven (as garden) rep- resents symbol of particular material properties which can be gained by anyways to fulfil the material needs. In this case, the Quran is to motivate the Moslems have the spiritual belief and perform good deed that this represents a symbol of revenge for them.Â Key words: Semiotics, Mitos, Ideologi, Surga, dan JannahÂ Â Â